2020
DOI: 10.21203/rs.3.rs-119031/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Receptors are Expressed on Human Platelets and the Effect of Aspirin on Clinical Outcomes in COVID-19 Patients

Abstract: Coronavirus disease-2019 (COVID-19) caused by SARS-CoV-2 is an ongoing viral pandemic marked by increased risk of thrombotic events. However, the role of platelets in the elevated observed thrombotic risk in COVID-19 and utility of anti-platelet agents in attenuating thrombosis is unknown. We aimed to determine if human platelets express the known SARS-CoV-2 receptor-protease axis on their cell surface and assess whether the anti-platelet effect of aspirin may mitigate risk of myocardial infarction (MI), cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 26 publications
0
42
0
1
Order By: Relevance
“…Observational studies on the use of aspirin in COVID19 patients have shown conflicting results. Chow et al [76] reported decreased mortality, ICU admission, and mechanical ventilation, but Sahai et al [77] found no change in mortality and an increased thrombotic risk in COVID19 patients taking aspirin. Current World Health Organization and Food and Drug Administration guidelines do not recommend stopping NSAIDs in symptomatic COVID19 patients [78,79].…”
Section: Safety Of Anti-inflammatory Drugs In Covid19mentioning
confidence: 99%
“…Observational studies on the use of aspirin in COVID19 patients have shown conflicting results. Chow et al [76] reported decreased mortality, ICU admission, and mechanical ventilation, but Sahai et al [77] found no change in mortality and an increased thrombotic risk in COVID19 patients taking aspirin. Current World Health Organization and Food and Drug Administration guidelines do not recommend stopping NSAIDs in symptomatic COVID19 patients [78,79].…”
Section: Safety Of Anti-inflammatory Drugs In Covid19mentioning
confidence: 99%
“…Accumulating data prove the relationship between COVID-19 and thrombosis [ 84 ]. The clinical and autopsy studies indicate that the risks of microvascular thrombosis, venous thromboembolism, and ischemic stroke are higher in COVID-19 patients [ 85 , 86 ]. Also, it was found that platelets have high affinity receptors for SARS-CoV-2, suggesting that platelets may participate in the development of COVID-19 [ 85 ].…”
Section: Covid-19 and Asamentioning
confidence: 99%
“…The clinical and autopsy studies indicate that the risks of microvascular thrombosis, venous thromboembolism, and ischemic stroke are higher in COVID-19 patients [ 85 , 86 ]. Also, it was found that platelets have high affinity receptors for SARS-CoV-2, suggesting that platelets may participate in the development of COVID-19 [ 85 ]. Thus, the application of antiplatelet drugs in the prophylaxis and treatment of COVID-19 and related complications might be a viable treatment strategy.…”
Section: Covid-19 and Asamentioning
confidence: 99%
“…Unless formal anticoagulation is indicated, (per guidelines contingent upon D-Dimer levels), we recommend 1 baby aspirin daily (81 mg) for purposes of reducing clot and sludging via platelet inhibition (unless aspirin in the patient is contraindicated). [68][69][70][71][72][73][74][75][76][77]…”
Section: Baby Aspirinmentioning
confidence: 99%